ANALISIS PENGARUH PARTISIPASI PENYUSUNAN ANGARAN TERHADAP KINERJA MANAJERIAL DINAS BINA MARGA KABUPATEN GROBOGAN DENGAN KETIDAKPASTIAN LINGKUNGAN DAN MOTIVASI SEBAGAI VARIABEL MODERATING - Kusumawati, Novi Nurkumala (STIE AUB Surakarta)
Managerial performance is one factor that can be used to improve organizational effectiveness. In order for these objectives to be achieved effectively it is necessary to pay attention to budgetary participation and greater motivation and environmental uncertainly in relation to decisions related to the budget. This research aims to know: 1) The influence of budgetary participation toward the managerial performance in Dinas Bina Marga sub-province Grobogan, 2) The influence of environmental uncertainly toward the managerial performance in Dinas Bina Marga sub-province Grobogan, 3) The influence of motivation toward the managerial performance in Dinas Bina Marga sub-province Grobogan, 4) environmental uncertainty moderates the effect of budgetary participation on managerial performance in Dinas Bina Marga sub-province Grobogan, 5) motivation moderates the effect of budgetary participation on managerial performance in Dinas Bina Marga sub-province Grobogan.The data are collected from 37 respondents by using a sensus method. They are analyzed through the research instruments such as a product moment test and the reliability test by using a Cronbach Alpha technique, classical assumption by using a normality method, heteroscedastisity and multicolinierity; the hypothesis test was analyzed by simple regression analysis, and absolute difference value test, determination coefficient (R2), t test, F test.The research result shows that 1) the influence of budgetary participation is positive and significant toward the managerial performance proved the research, 2) the influence of environmental uncertainly is positive and significant toward the managerial performance proved the research, 3) the influence of motivation is positive and significant toward the managerial performance proved the research, 4) environmental uncertainty moderates the effect of budgetary participation on managerial performance in significantcy 10%, 5) motivation moderates the effect of budgetary participation on managerial performance unproved the research, 6) Coefficient determination show that total R Square is 0.729, the meaning managerial performance variable explained by aÂ budgetary participation with environmental uncertainty and motivation as moderating variable is 72,9% and while its remain 27,1% is explained by other variable which is not involved in the regression model such as commitment organizational, job satisfaction.Key word: budgetary participation, environmental uncertainty, motivation, managerial performance.